Синтез, структура та властивості нанокомпозитів на основі високодисперсного кремнезему, модифікованого оксидами цирконію та церію - Sulim, I. Ya.; Borysenko, M. V.; Tinkov, V. A.; Borysenko, L. I. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2009)
The structure peculiarity and physicochemical properties of synthesized ZrO2 - CeO2/SiO2 nanocomposites were studied using XRD, IR-FOURIER spectroscopy, differential thermal analysis and SEM-EDS. It was shown, that the simultaneous modifying of a silica surface with Zr(acac)4 and Ce(acac)3 and the subsequent calcination up to 550 °C leads to formation roentgenamorphous ZrO2 and CeO2 oxides. Growth of the size of xZrO2 ■ yCeO2 crystallites from 4 up to 23 ran was found with increasing of calcination temperature of nanocomposites.